Influence of Air Gaps in Fastening System at KTMB Electrified Double Track in Kluang - Nordin, Nor Farah Amira; Ganasan, Reventheran; Mohamed Jizi, Siti Zarini; Mohd Fozi, Nadzirah (Progress in Engineering Application and Technology, 2024)
YTL Construction and SIPP Rail Sdn. Bhd. are jointly undertaking a 192-kilometer electrified double track project stretching from Gemas to Johor Bahru, encompassing Segamat, Kluang, Kulai, and Kempas Baru districts. However, the fastening system at the KTMB Kluang site has revealed air gaps, posing concerns for long-term track quality. This study aims to assess the impact of these gaps on quality, analyze potential causative factors’ frequency, and evaluate the effectiveness of quality risk assessment based on air gap occurrences. Methodologically, it involves meticulous 100-meter track inspections, acquiring fastening component details from YTL’s server pending permission, and incorporating testing reports. It concludes that air gaps stem from poor workmanship and subpar material quality, with misalignment during installation and weak materials contributing.